Optimization of Financing in Joint Business Savings and Loan Cooperatives as a Driving Force of the Economy - Gano, Irwan; Daud; Al-Munip; Nisak, Sayida Khoiratun; Fatimah, Siti (CV. Civiliza Publishing, 2025)
This study examines the role of the Joint Savings and Loan Cooperative (KSP-UB) in Mendahara Subdistrict in promoting local economic development, particularly for micro and small business actors. Using a qualitative descriptive approach, the study describes how the cooperative provides accessible, affordable, and tailored financing to its members, thereby strengthening their business capacity and driving village economic growth. Beyond financing, the cooperative also acts as a facilitator for human resource development through training in financial management, digital marketing, and product innovation. KSP-UB supports member product marketing by expanding market access through both traditional and digital networks. The business networks formed among members enhance solidarity, production efficiency, and bargaining power in the market. The findings indicate that the cooperative is not only an alternative financial institution but also a strategic partner that empowers and strengthens the economic independence of the community in an inclusive and sustainable manner. These findings contribute significantly to understanding the role of cooperatives in microeconomic development in rural areas